2021
DOI: 10.46431/mejast.2021.4408
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sensitized Silver Nanoparticles on Pretreated Polyester and Silk Fabrics with Eco-friendly Mixed Gas Plasma

Abstract: This article studies the effect of surface modification of polyester (PET) and silk fabrics by exposing to cold plasma discharge. The cold plasma discharge was proceeded using oxygen/Argon mixed gas as a working gas and different plasma device parameters have been studied such as: different time, different current and different hydrostatic pressure. Treated fabrics are characterized by the measurements and evaluation of mechanical properties, air permeability, Electron Spin Resonance (ESR) and the changes in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[30] The increase in hydrophilicity in several fibres such as polyester (PET), polyethylene (PE) [31], polypropylene (PP, polytetrafluoroethylene (PTFE), silk. [32] It was also observed that of when wool fabric treatment with Corona discharge the possibility to be worn next to skin increases due to high absorbency. [33] Plasma treatment significantly improved the mechanical characteristics of natural fibres.…”
Section: Plasma Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] The increase in hydrophilicity in several fibres such as polyester (PET), polyethylene (PE) [31], polypropylene (PP, polytetrafluoroethylene (PTFE), silk. [32] It was also observed that of when wool fabric treatment with Corona discharge the possibility to be worn next to skin increases due to high absorbency. [33] Plasma treatment significantly improved the mechanical characteristics of natural fibres.…”
Section: Plasma Modificationsmentioning
confidence: 99%
“…The treated silk samples with oxygen and oxygen/argon mixed gas plasma and/or nano-silver treated silk samples dyed with natural Red Lac dye that gave high color intensity and high fastness properties for light and washing for treated fabrics. [32,39] The color strength and color fastness properties of dyed cotton treated by Low-temperature plasma samples with madder and weld natural dyes under various conditions were improved. [40] Pre-surface modification of cotton, linen and viscose with N2-plasma improved the antibacterial functionalization with enhanced durability due to formation of new active binding sites such as -NH2 groups which loaded by nano-silver to acquire a fabrics antibacterial properties.…”
Section: Plasma Modificationsmentioning
confidence: 99%